Dynamic Information Validation Scheme in Internet of Things: Software Agent based Approach - PH, Sharanappa; Kakkasageri, Mahabaleshwar S (International Journal of Computer Sciences and Engineering, 2021)
The Internet of Things (IoT) and its various application domains are drastically changing people's lives by providing intelligent services that will eventually become an intrinsic part of their daily environment. The data flows received from various actuators and sensors are used to power the IoT services. The accuracy and security of sensor data supplied across the Internet of Things system is a vital aspect in ensuring that IoT services work properly. As a result, data validation in a remote IoT network is becoming increasingly important. Even though the immediate option of establishing duplicate identical systems can provide validation, real-world change limitations can make this difficult, if not impossible. So here in this paper we have proposed an intelligent validation scheme. We have evaluated the performance and effectiveness of proposed scheme by comparing with an existing technique that uses BL and KP-ABE scheme. In terms of time necessary to sense the data, data gathering time, time required to validate the data, and end to end delay, the suggested method outperforms the existing validation methodology.